Pengaruh Kinerja Lingkungan, Green Corporate Governance, Leverage, Dan Investment Opportunity Set Terhadap Integritas Laporan Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Andhika Arafah; Rosiyana Dewi (AkMen JURNAL ILMIAH, 2023)
This study refers to problems related to financial statement integrity which are influenced by various factors. So researchers want to re-examine issues related to financial statement integrity. There are still many variables that affect the integrity of the financial statement. And related to this, it attracted researchers to re-examine to find out whether there is a relationship between the variables Environmental Performance, Green Corporate Governance, Leverage, and Investment Opportunity Set on Financial Statement Integrity with Firm Size as control variables. The analytical method used by the researcher is Generalized Least Square with the Purposive Sampling technique and the data used is Annual Report and Sustainability Report data for non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. From the results of the research, It has been shown that the Environmental Performance, Green Corporate Governance, Leverage, and Investment Opportunity Set variable has effect on financial statement integrity.